A novel method combining VAT photopolymerization and casting for the fabrication of biodegradable Zn–1Mg scaffolds with triply periodic minimal surface. (May 2023) - Chen, Boxu; Sun, Xiaohao; Liu, Debao; Tian, Hua; Gao, Jingjun
Abstract: Zinc alloy porous scaffolds are expected to be the next generation of degradable orthopedic implants attributed to their suitable degradation rate. However, a few studies have thoroughly investigated its applicable preparation method and functionality as an orthopedic implant. This study fabricated Zn–1Mg porous scaffolds with triply periodic minimal surface (TPMS) structure by a novel method combining VAT photopolymerization and casting. As-built porous scaffolds displayed fully connected pore structures with controllable topology. The manufacturability, mechanical properties, corrosion behaviors, biocompatibility, and antimicrobial performance of the bioscaffolds with pore sizes of 650 μm, 800 μm, and 1040 μm were investigated, and then compared and discussed with each other. In simulations, the mechanical behaviors of porous scaffolds exhibited the same tendency as the experiments. In addition, the mechanical properties of porous scaffolds as a function of degradation time were studied through a 90-day immersion experiment, which can provide a new option for analyzing the mechanical properties of porous scaffolds implanted in vivo. The G06 scaffold with lower pore size presented better mechanical properties before and after degradation compared with G10. The G06 scaffold with the pore size of 650 μm revealed good biocompatibility and antibacterial properties, which makes it possible to be one of the candidates for orthopedic implants. Graphical abstract: Image 1 Highlights: The novel method through combining VAT photopolymerization and casting was developed on an open commercial machine. Porous Zn–1Mg scaffolds with triply periodic minimal surface (TPMS) could be processed by the novel method accurately. Biodegradable Zn–1Mg scaffolds presented excellent mechanical properties after 90 days of biodegradation. Biodegradable Zn–1Mg scaffolds showed good biocompatibility and antibacterial performance.